Heart rate variability in idiopathic dilated cardiomyopathy: relation to disease severity and prognosis. Issue 2 (February 1997) - Yi, G.; Goldman, J. H.; Keeling, P. J.; Reardon, M.; McKenna, W. J.; Malik, M.
Abstract : OBJECTIVE: To assess the clinical importance of heart rate variability (HRV) in patients with idiopathic dilated cardiomyopathy (DCM). PATIENTS AND METHODS: Time domain analysis of 24 hour HRV was performed in 64 patients with DCM, 19 of their relatives with left ventricular enlargement (possible early DCM), and 33 healthy control subjects. RESULTS: Measures of HRV were reduced in patients with DCM compared with controls (P < 0.05). HRV parameters were similar in relatives and controls. Measures of HRV were lower in DCM patients in whom progressive heart failure developed (n = 28) than in those who remained clinically stable (n = 36) during a follow up of 24 (20) months (P = 0.0001). Reduced HRV was associated with NYHA functional class, left ventricular end diastolic dimension, reduced left ventricular ejection fraction, and peak exercise oxygen consumption (P < 0.05) in all patients. DCM patients with standard deviation of normal to normal RR intervals calculated over the 24 hour period (SDNN) < 50 ms had a significantly lower survival rate free of progressive heart failure than those with SDNN > 50 ms (P = 0.0002, at 12 months; P = 0.0001, during overall follow up). Stepwise multiple regression analysis showed that SDNN < 50 ms identified, independently of other clinical variables, patients who were at increased risk of developing progressive heart failure (P = 0.0004). CONCLUSIONS: HRV is reduced in patients with DCM and related to disease severity. HRV is clinically useful as an early non-invasive marker of DCM deterioration.